Corporate finance : economic foundations and financial modeling - Michelle R. Clayman (John Wiley & Sons, 2024)
The book that fills the practitioner need for a distillation of the most important tools and concepts of corporate finance. In today's competitive business environment, companies must find innovative ways to enable rapid and sustainable growth not just to survive, but to thrive